RISK FACTORS OF SUCCESSFUL SUICIDE ATTEMPTS IN PUNJAB - Naz, Fauzia (Journal of Postgraduate Medical Institute, 2016)
Objectives: To explore the socio-demographic factors of successful suicide attempts in Punjab, Pakistan. Methodology: Archival research design was used to gather data in the form of reports of successful suicide commitment were collected from "Daily Express" for ten months from September, 2014 to June, 2015. All possible information related to gender, age, marital status, causes of suicide and mode of suicide was gathered. Data in only one newspaper was included to avoid repetition of news. News with missing important demographic information was excluded. Data were analyzed using descriptive statistics. Results: Out of total 87, more male 50(57.5%) than females 37(42.5%) committed suicide. Most victims of suicide fell in the age range between 20-29 years i.e., 26(29.9%). Mostly unmarried individuals 43(49.4%) committed suicide in comparison with the married individuals who were 33(37.9%). Most of the suicides were committed because of domestic quarrels 45(51.7%). Among different modes of committing suicide, use of poison pills (used as pesticides for wheat) were the highest 48(55.2%). Conclusion: Young males, unmarried individuals and domestic problems were the leading factors for successful suicide attempts. Use of poison pills was the commonest mode of suicide.